PENGEMBANGAN MEDIA PEMBELAJARAN GAMIFIKASI BERBANTUAN GENIALLY DAN EDUCAPLAY DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN CACAH - Sevina Dwi Permata Putri; Sri Rahayu; Nyamik Rahayu Sesanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low interest in learning mathematics among students occurs because teachers still use conventional learning media that are less interactive and engaging. This study aims to determine the feasibility, practicality, and effectiveness of gamified learning media assisted by Genially and Educaplay on addition and subtraction of whole numbers to increase the learning interest of second-grade students. This research employed the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects included students, classroom teachers, and validators consisting of material, media, and language experts. The instruments used were validation questionnaires, student and teacher response questionnaires, and learning interest questionnaires, with data collected through observation, questionnaires, and documentation. The analysis results showed that the learning media were categorized as “very feasible” with a percentage of 87.5% from material experts, 95.83% from media experts, and 100% from language experts. The practicality of the media was in the “very practical” category with a percentage of 81.94% from teachers and 94.8% from students. The effectiveness of the media was categorized as “effective” with a percentage of 87.41%. Thus, gamified learning media assisted by Genially and Educaplay are proven to be feasible, practical, and effective in increasing students’ learning interest in addition and subtraction of whole numbers, making it a potential alternative for interactive mathematics learning in lower elementary grades.